The Crisis of Child Custody: A History of the Birth of Family Law in England - Wright, Danaya C. (Columbia Journal of Gender and Law, 2002)
In 1856 the House of Lords engaged in extensive debates over the introduction of a bill that would reform the law of divorce in England. Numerous critics of the law complained that the cost and complexities of jurisdiction foreclosed the remedy to the poor, while many women complained that the dual standards for obtaining a divorce were unfair to women. To get a divorce, a husband (and it was only husbands) had to bring a criminal conversation action against his wife’s lover and get an award of damages, obtain a legal separation in the ecclesiastical courts, then petition both Houses of Parliament for a separate bill of divorce allowing him to remarry. The total cost could easily surpass £1,000. A woman generally could not get a divorce, nor could she sue her husband’s mistress for alienation of his affections. She could only obtain a legal separation in the ecclesiastical court that gave her no right to remarry, and any alimony order out of the ecclesiastical court was unenforceable without a petition for enforcement in the Royal Courts. It was not unexpected, therefore, that during a period of intense law reform, Britons would challenge the unwieldy and uneven laws of divorce. In the 1856-57 debates, Parliament focused primarily on two issues: simplifying the process in order to make justice available to a wider class of litigants and equalizing the rights of husbands and wives to seek absolute divorce. In the end, a bill was passed in 1857, to take effect January 1, 1858, establishing a unitary court with jurisdiction over all matrimonial matters, thus expanding the court’s availability to a greater percentage of the population, though still not bringing justice to the poor who could not afford the fees or the trip to London where the court sat. Furthermore, in a compromise between those who wanted the law to imitate the Scottish law of divorce granting both husbands and wives equal rights to seek divorce, and those who wanted to entirely foreclose the possibility to wives, the final bill granted husbands the right to an absolute divorce upon evidence of mere adultery by their wives, but wives needed to prove aggravated adultery to petition for the same remedy. This law stood relatively unchanged until 1937 when desertion, cruelty, habitual drunkenness, and incurable insanity were added as fault bases that stood alone.